2021
DOI: 10.1016/j.ejphar.2020.173836
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the mechanism of arbidol binding and inhibition of SARS-CoV-2: Insights from atomistic simulations

Abstract: The COVID-19 pandemic has spread rapidly and posed an unprecedented threat to the global economy and human health. Broad-spectrum antivirals are currently being administered to treat severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). China's prevention and treatment guidelines suggest the use of an antiinfluenza drug, arbidol, for the clinical treatment of COVID-19. Reports indicate that arbidol could neutralize SARS-CoV-2. Monotherapy with arbidol is found to be superior to lopinavir-ritonavir or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 74 publications
0
62
0
1
Order By: Relevance
“…Molecular dynamics simulation analyses revealed that Arbidol may bind to both RBD and ACE2 at the contacting interface, with a higher affinity for RBD. The presence of Arbidol may impair the interactions between S and ACE2 to prevent viral entry [96]. Moreover, several fusion-inhibitory peptides have been developed with potent antiviral efficacies in vitro which bind to the HR1 domain of S2 subunit and prevent the conformational changes required for membrane fusion [97][98][99][100][101][102].…”
Section: Antibodies Vaccines and Inhibitorsmentioning
confidence: 99%
“…Molecular dynamics simulation analyses revealed that Arbidol may bind to both RBD and ACE2 at the contacting interface, with a higher affinity for RBD. The presence of Arbidol may impair the interactions between S and ACE2 to prevent viral entry [96]. Moreover, several fusion-inhibitory peptides have been developed with potent antiviral efficacies in vitro which bind to the HR1 domain of S2 subunit and prevent the conformational changes required for membrane fusion [97][98][99][100][101][102].…”
Section: Antibodies Vaccines and Inhibitorsmentioning
confidence: 99%
“…It was proposed that the binding of Arbidol induces structural rigidity in the virus glycoprotein, resulting in restriction of the conformational rearrangements associated with membrane attachment and virus entry. 58 In a related study, MD simulations and structural analyses were carried out to highlight that Arbidol blocks the S-protein trimerization, which is crucial for host cell adhesion and hijacking. 59 A supervised MD study further explored the druggability of the SARS-CoV-2 S-protein, which showed that six FDA-approved drugs were capable of significantly blocking the RBD/ACE2 interaction.…”
Section: Drug Design and Discoverymentioning
confidence: 99%
“…All the ligands were docked at the ACE2 binding site to investigate their best binding pose and binding energy. As many studies have reported an anti-influenza drug, Umifenovir, to be effective against ACE2-Spike protein interactions and is currently being tested in clinical trial against SARS-CoV-2 (Choudhary & Silakari, 2020 ; Padhi et al., 2021 ), so we chose this drug as a positive control for the computational study. When we docked Umifenovir at ACE2 binding site, the docking score in the best binding pose was −4.31 kcal/mol and it was participating in the interaction by making hydrogen bond contacts with Lys31 and Glu35 ( Figure 2(A) ).…”
Section: Resultsmentioning
confidence: 99%